Demonic and Divine Attributions around COVID-19 Vaccines: Links with Vaccine Attitudes and Behaviors, QAnon and Conspiracy Beliefs, Anger, Spiritual Struggles, Religious and Political Variables, and Supernatural and Apocalyptic Beliefs - Exline, Julie J. (Religions, 2022)
Given the prevalence of supernatural beliefs in the United States, some people may believe that God or the devil influenced people to create or receive COVID-19 vaccines. In an Internet sample of 3196 U.S. adults (with many preregistered hypotheses), divine vaccine attributions were more common than demonic attributions. Demonic vaccine attributions were linked with more anti-vaccination attitudes and lower odds of vaccination, whereas divine attributions showed the opposite pattern. Demonic (but not divine) attributions showed consistent positive connections with conspiracy beliefs (including QAnon), anger toward people and organizations seen as pro-vaccine, and seeing one’s political opponents as enemies and as evil. Demonic attributions were also linked with more anxiety, depression, and spiritual struggle, and lower agreeableness and social desirability. Both demonic and divine attributions related positively to political conservatism, religious fundamentalism, Christian nationalism, authoritarian aggression, and traditional masculinity beliefs. Demonic (but not divine) attributions were also associated with being younger and having less education. Both demonic and divine vaccine attributions correlated positively with religiousness, belief in God and the devil, and seeing these entities as powerful, able to work through natural events, and intervening often in the world. Demonic and divine attributions also related positively to belief in heaven and hell, seeing many people as destined for hell, seeing life as a cosmic battle between good and evil, and apocalyptic or "end times" beliefs.